Rethinking Rethinking the Good - Temkin, Larry S. (Journal of moral philosophy, 2015)
This article discusses many issues raised by Munoz-Dardé, Katz, Ross, and Kagan. In doing this, I accept many of their claims, but reject others. I contend that the Essentially Comparative View can make genuine comparisons, deny that a contractualist approach helps with my book’s puzzles, and grant that my book’s central results are difficult to comprehend. I note important differences between economists’s impossibility results and my own, but accept that they may illuminate each other, using Sen’s Paradox of the Paretian Liberal to illustrate this. I consider my work’s implications for the Sorites Paradox, as well as famous deontological cases. I also significantly reassess the Narrow Person-Affecting View, and some of my responses to Parfit and Broome. Finally, I stress my book’s many arguments challenging the Axioms of Transitivity, the high costs of retaining such axioms, and the importance of not prematurely choosing between highly plausible views that are inconsistent.